Cultural Factors Causing Differences in Quality Education - Pokharel, Anil Kumar; Paudel, Janardan (Researcher: A Research Journal of Culture and Society, 2014)
This paper presents introduction of school and college level culture in educational systems in Nepal as well as other factors that have been the cause in creating differences in the quality of education in the schools and colleges in Nepal. It explores the points like different types of schools and colleges, regional diversity, environment, teacher’s qualification, physical facilities, class management, conventional feeling, and conclusion. The analysis and interpretation is made according to some existing literature and our own experience in the field of teaching for a long time. DOI: http://dx.doi.org/10.3126/researcher.v1i2.9881 Researcher 1(2) 2013: 1-10